THE PROHIBITION OF ABUSE OF RIGHTS IN THE DRAFT CIVIL CODE OF THE REPUBLIC OF SERBIAN - Živorad (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
This paper describes, explains and critically evaluates the proposed Article 20 provision of the civil rights` abuse from of the Draft Serbian Civil Code. First, its institutional development is briefly presented and contemporary theoretical dilemmas about its nature are analysed. Then, the relevant Serbian and comparative lege lata and lege ferenda provisions are compared. Finally, the proposed solution is critically evaluated against the following criteria: the foundation in the tradition of civil case-law and literature, adequacy to the modern theory of civil law, content, and informativeness, legal and logical consistency.The research results expose the authors’ choice to formulate the new provision on the lege lata, enriched with the concept of the harm to the others and with the subjective manifestations of the civil rights` abuse. This solution is criticised here for the lack of an enumeration of the abuse manifestations that have been recognized in the case-law and the literature, and the lack of modern approach that is based on the theory of internal limitations of civil rights.Having the premises in the modern civil law literature, a different lege ferenda provision is proposed here to more clearly express the nature of this institution and guide civil courts in the civil law interpretation.
Keywords: civil rights abuse; prohibition; subjective and objective approach; inner and outer theory